"Gender Refugees" in South Africa: The "Common-Sense" Paradox. Issue 1 (April 2018) - Camminga, B
South Africa is the only country on the African continent that constitutionally protects transgender asylum seekers. In light of this, it has seen a marked rise in the emergence of this category of person within the asylum system. Drawing on research carried out between 2012 and 2015, I argue that transgender-identified refugees or "gender refugees" from Africa, living in South Africa, rather than accessing refuge continue to experience significant hindrances to their survival comparable with the persecution experienced in their countries of origin. I argue this is in part due to the nature of their asylum claim in relation to gender as a wider system of "common-sense" dichotomous administration, something which remains relatively constant across countries of origin and refugee-receiving countries. Rather than being protected gender refugees, because they are read as violating the rules of normative gender, they find themselves paradoxically with rights, but unable to access them.